Health-Related Quality of Life as Measured by the 12-Item Short-Form Survey Among Adults With Community-Acquired Bacterial Pneumonia who Received Either Lefamulin or Moxifloxacin in 2 Phase III Randomized, Double-Blind, Double-Dummy Clinical Trials. (3rd June 2020) - Lodise, Thomas P; Colman, Sam; Alexander, Elizabeth; Stein, Daniel S; Fitts, David; Goldberg, Lisa; Schranz, Jennifer
Abstract: Background: Interest in patient-reported outcomes (PROs) as part of benefit–risk assessment for new drug approvals is increasing. Lefamulin is the first intravenous (IV) and oral pleuromutilin antibiotic for treatment of adults with community-acquired bacterial pneumonia (CABP). Assessment of health-related quality of life (HRQoL) was prospectively incorporated in its CABP trials (Lefamulin Evaluation Against Pneumonia [LEAP] 1 and 2) via the 12-Item Short-Form Survey (SF-12), a widely used PRO that measures general health status in 8 domains. Methods: HRQoL was evaluated by SF-12 at baseline and test of cure (TOC; 5–10 days after the last study drug dose) in patients who received lefamulin or moxifloxacin in LEAP 1 (IV/oral treatment) and LEAP 2 (oral-only treatment). SF-12 outcomes included the 8 domains, physical component and mental component summary scores, and the Short-Form Six-Dimension health utility score. Results: Analysis included 1215 patients (lefamulin: n = 607; moxifloxacin: n = 608). At baseline, all mean SF-12 scores in both treatment groups were well below the United States reference mean. Clinically meaningful and significant improvements from baseline to TOC were observed in all SF-12 scores. No significant differences in mean score improvements from baseline to TOC between treatment groups were observed. SF-12 score improvements at TOC across predefined subgroups were comparable between treatment groups. Conclusions: Results indicate that adults with CABP experienced comparable HRQoL improvements with lefamulin relative to moxifloxacin, and treatment with either agent resulted in returns to population norm HRQoL levels. These data suggest that lefamulin is a potential alternative to moxifloxacin for treatment of adults with CABP.